SOSIALISASI KOMUNIKASI PEMASARAN SEBAGAI UPAYA PENINGKATAN PENJUALAN TERNAK IKAN LELE - Khalish Khairina; Mukhtasar; Ainun Mardhiah; Husni Kamal; Angga Syahputra; Uswatun Hasanah (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
The conventional marketing system which still distributes their product from mouth to mouth and social medial using hasn’t maximized yet were problems that found in livestock business owned by Desa Uteunkot is contributing this community services activities. The purpose of this activity is educating mitra about the importance of marketing communication to reach out more consumer. The implementation method used is socialization to the society in Desa Uteunkot. The number of this socialization participants was 25 participants. After this community service implementation, there is an increase in catfish sales volume in the amount of 11%.